Tax Competition with Two Tax Instruments - and Tax Evasion - Johannes Becker; John D. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2021)
We consider a world in which countries apply optimal taxes on mobile capital and savings (like in Bucovetsky and Wilson, 1991). Firms and savers may underreport income in order to avoid or evade taxation. We show that, even in the presence of underreporting, the equilibrium under tax competition may still be constrained-efficient (in the sense that there is no scope for welfare enhancing tax coordination). This is the case if the marginal social costs of underreporting savings and investment income are equal. The model demonstrates that, if source-based taxes on capital are inefficiently low, as is often assumed, taxes on savings must be inefficiently high. Constrained-efficient tax policy minimizes the social cost of underreporting. The results are robust to introducing taxes on profit or on labor income, if these types of income can be underreported as well. We conclude that commonly held assumptions on the need for coordination under tax competition need to be revised or qualified.
Keywords: H25; H32; H87; 330; tax competition; social welfare; tax coordination